Influence of water stress and lead on yield, mineral nutrition composition and relative water content in Indian spinach (Basila alba L.) (Bangladesh Journal of Scientific Research, 2011)
Key words: Water stress; lead treatment; mineral uptake; relative leaf water contentBangladesh J. Sci. Res. 23(2): 145-154, 2010 (December)